2020
DOI: 10.1038/s41598-020-79400-0
|View full text |Cite
|
Sign up to set email alerts
|

Gigantol ameliorates CCl4-induced liver injury via preventing activation of JNK/cPLA2/12-LOX inflammatory pathway

Abstract: Arachidonic acid (AA) signaling pathway is an important constituent of inflammatory processes. In our previous study, it was found that dihydro-stilbene gigantol relieved hepatic inflammation in mice with CCl4-induced acute liver injury. This study aimed to investigate the involvement of arachidonate metabolic cascade in this process. Our results showed CCl4 activated AA metabolism with the evidence of cPLA2 phosphorylation, which was dependent on the MAPK/JNK activation. Pretreatment with JNK inhibitor SU3327… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…and Bulbophyllum leopardium with reference to antifibrotic activity in vitro [ 30 ], while marylaurencinol-A ( 4 ) was isolated from Cymbidium Great Flower “Marylaurencin” with antimicrobial activities [ 11 ]. Gigantol ( 7 ) and tristin ( 8 ) have mainly been referred to as isolated metabolites from Dendrobium sp., with gigantol displaying a wide range of bioactivities, including anti-oxidant, anti-mutagen, anti-platelet aggregation, anti-spasmodic and anti-ageing effects [ 41 , 42 ]. Furthermore, in the chemical category of 1,4-phenanthrenequinones, 5-hydroxy-2-methoxy-1,4-phenanthrenequinone ( 5 ) and ephemeranthoquinone-B ( 6 ) were isolated from Cymbidium sp., with 5-hydroxy-2-methoxy-1,4-phenanthrenequinone showing cytotoxic activity against human cell lung cancer (NCI-H187) cell line [ 21 ] and ephemeranthoquinone-B showing antimicrobial and antioxidant activities in vitro [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…and Bulbophyllum leopardium with reference to antifibrotic activity in vitro [ 30 ], while marylaurencinol-A ( 4 ) was isolated from Cymbidium Great Flower “Marylaurencin” with antimicrobial activities [ 11 ]. Gigantol ( 7 ) and tristin ( 8 ) have mainly been referred to as isolated metabolites from Dendrobium sp., with gigantol displaying a wide range of bioactivities, including anti-oxidant, anti-mutagen, anti-platelet aggregation, anti-spasmodic and anti-ageing effects [ 41 , 42 ]. Furthermore, in the chemical category of 1,4-phenanthrenequinones, 5-hydroxy-2-methoxy-1,4-phenanthrenequinone ( 5 ) and ephemeranthoquinone-B ( 6 ) were isolated from Cymbidium sp., with 5-hydroxy-2-methoxy-1,4-phenanthrenequinone showing cytotoxic activity against human cell lung cancer (NCI-H187) cell line [ 21 ] and ephemeranthoquinone-B showing antimicrobial and antioxidant activities in vitro [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This would suggest that baicalein mediated inhibition of CCl 4 -induced ferroptosis is partly dependent on the inhibition of ALOX12 activity. Previous studies also showed that inhibition of ALOX12 gene expression also contributed to inhibition of inflammatory response [ 71 ]. Whether the inhibition of ALOX12 gene expression contributes significantly to the inhibitory effect of baicalein on CCl 4 –induced inflammatory still requires further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, the oxidative stress response of iRhom2-knockout mice did not increase after alcohol stimulation compared to the nonalcoholic treatment group. JNK activation is a key pathway leading to oxidative stress [ 50 , 51 , 52 , 53 ]. Moreover, iRhom2 has been previously proven to regulate JNK and induce the oxidative stress response to liver injuries [ 54 ].…”
Section: Discussionmentioning
confidence: 99%